AM-251, A Cannabinoid Antagonist, Modifies the Dynamics of Sleep–Wake Cycles in Rats - Bogáthy, Emese; Papp, Noémi; Vas, Szilvia; Bagdy, György; Tóthfalusi, László (Frontiers in Pharmacology, 2019)
Study objectives: a) To describe the microarchitecture of wakefulness and sleep following administrations of 5 and 10 mg/kg AM-251 in rats. b) To develop a new statistical method to follow bout-to-bout dynamics. Method: Wistar rats (n = 6) had been equipped with electroencephalography (EEG) and electromyography (EMG) electrodes. Following their recovery and habituation after the surgery, the animals were injected with vehicle and 5 and 10 mg/kg AM-251 intraperitoneally and EEG, EMG and motor activity was analyzed for the subsequent three hours. Results: AM-251 induced a dose- and time-dependent increase in the number of bouts in active wake (AW) and it decreased this number in all other vigilance states except in passive wake (PW). In contrast, the bout duration in PW compensatory decreased. The effect of AM-251 on the sleep transition dynamics was monitored with a new tool we call "transition heatmap". The analysis of bout trajectories with transition heatmaps reveals a highly organized pattern. Conclusion: AM-251 selectively influences the frequency of vigilance state transitions, but it has no direct impact on the state lengths. AM-251 markedly changed the state transition dynamics, which was visualized with the help of state transition heatmaps.